Comparisson On The Effectiveness Of Cooperative Learning Model Of Numbered Heads Together (NHT) And Team Assisted Individualization(TAI) In Geometry - Ruslan Djaya (Daya Matematis: Jurnal Inovasi Pendidikan Matematika, 2013)
The study is an experiment research which aims at examining (1) the implementation of cooperative learning model of TAI (Team Assisted Individualization) type and NHT (Numbered Head Together) type; (2) the effectiveness of learning model of TAI type based on the aspects of learning outcomes, students’ activity, and students’ response; (3) the effectiveness of learning model of NHT type based on the aspects of learning outcomes, students’ activity, and students’ response; and (4) the comparison on the effectiveness of cooperative learning model of TAI type and NHT type in Geometry of grade VII students at SMPN 4 Sungguminasa. The study was conducted in grade VII at SMPN 4 Sungguminasa in Gowa on the second semester of academic year 2012/2013. Samples were selected randomly and obtained two classes out of thirteen classes. The chosen classes implemented the TAI type and the other one implemented the NHT type in Geometry lesson. The effectiveness of learning which consisted of thee aspect, namely learning outcomes of students, learning activity of students, and students’ response were examined. The result of study reveal that (1) the implementation of cooperative learning model of TAI type in geometry was conducted well with the mean score 3.60; (2) the implementation of cooperative learning model of TAI type in Geometry was effective based on the aspects of a students’ learning outcomes with the mean score of post-test greater than the pre-test by 79.47 ≥ KKM and students’ mastery of the lesson was 88.89% ≥ 85%, b) students’ learning outcomes with the implementation of activity 3.24, and c) students’ response with the mean score  3.57 (positive category); (3) the implementation of cooperative learning model of NHT type was conducted well with the mean score of the implementation 3.69; (4) the implementation of cooperative learning model of NHT type was effective based on the aspect of a) students’ learning outcomes with the mean score of post-test was greater than pre-test by 78.64 ≥ KKM and students’ mastery of the lesson was 86.11% ≥ 85%, b) students’ response with the mean score 3.46; (5) based on the set effective criteria, it is confirmed that the geometry lesson by determining the circumstance and area of square and triangle and used in solving the problem on the implementation of cooperative learning model of TAI type is better than NHT type of grade VII students at SMP where the three aspects, namely students’ learning outcomes, students’ activity, and students’ response were better than the TAI type.